Right hemicolectomy with D3 lymph node dissection for right-sided transverse colon cancer using the Senhance robotic system: a case report - Atsuko Kataoka; Yasumitsu Hirano; Hiroka Kondo; Satoshi Shimamura; Masahiro Kataoka; Masahiro Asari; Takatsugu Fujii; Shintaro Ishikawa; Toshimasa Ishii; Shigeki Yamaguchi (Surgical Case Reports, 2020)
Abstract Background The evolution of remote systems and artificial intelligence technology has led to increase in robotic surgeries. One system used in this case report is the Senhance robotic system. The most important premise for using robotic surgery in cancer therapeutics is to ensure oncological safety. Similar to conventional laparoscopic surgery, robotic surgery needs to be a reliable and secure surgical procedure, such as complete mesocolic excisions with central vascular ligations in Western countries or D3 lymph node dissections (dissection of the lymph nodes that locates from the origin to the terminal branch of the main feeding artery of cancer) in Japan. Case presentation A 76-year-old man underwent clinical examination for severe anemia. He was diagnosed with transverse colon cancer of tumor (T)3, node (N)1a, metastasis (M)0 cancer stage IIIA. A right hemicolectomy with D3 lymph node dissection using the Senhance surgical system was performed. The operative time was 313 min and the estimated blood loss was 5 ml. He was discharged from our hospital 12 days after the surgery without any complications. What is the remarkable of this report, not only mobilization of right colon but also D3 lymph node dissection and vascular ligation were performed intraperitoneally by using Senhance robotic system as conventional laparoscopic surgery. We tried using fourth robotic arm to accomplish lymphadenectomies and middle colic artery dissection. A right hemicolectomy with D3 dissection using the Da Vinci surgical system was reported. Another report of a right hemicolectomy performed with the Senhance robotic system was identified; however, in that study, lymph node dissections were not performed intraperitoneally. Conclusions Therefore, to our knowledge, this is the first report using the Senhance robotic system for right hemicolectomy with D3 dissection. We hope that our case report will assist in the establishment of this robotic procedure in surgical practice.